Research of shape stability of the knitted fabric for fencing clothing under dynamic and static loads - Харченко, Юлія Михайлівна; Дмитренко, Людмила Андріївна; Білоцька, Лариса Борисівна; Стаценко, Володимир Володимирович; Очеретна, Лариса Валентинівна (Technology audit and production reserves, 2016)
Shape stability of the knitted fabric for making fencing clothing under static and dynamic loads is investigated. The study is carried out to further develop methods that will predict the shape stability of the clothing for sport fencing during wearing. It is established that irreversible deformation of the test material under uniaxial tension and stress by the standard method (according to GOST 8847-85) did not occur. Results of experimental wearing showed the presence of irreversible fabric deformation in the different parts of clothing from 1 to 4,5 %, which is the reason assert the impossibility of objective evaluation and prediction of the properties of investigated fabric during wearing. The values of limit stretching and constant load (60 and 80 N) are calculated using the «load-extension» diagram. Irreversible deformation of investigated fabric at the time of a balanced state is defined for given parameters of the constant multi-cycle load. It is analyzed and shown that the performance measurement results of the fabric deformation for multi-cycle stretching using laboratory method and results of measurement of these parameters for products that have been in a wearing for a year, are convergent. The proposed test method simulates the load on the clothing and changes their linear dimensions during the wearing. Established research parameters can be used in the method of determining and prediction of the shape stability of fencing clothing during the wearing.